2012
DOI: 10.1159/000343973
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance Genotype Trend and Its Association with Host Clinical Characteristics in Respiratory Isolates of <b><i>Haemophilus influenzae</i></b>

Abstract: Background: β-Lactam resistance genotype trends in clinical isolates of Haemophilus influenzae and their correlation with the clinical background were analyzed. Methods: Five hundred and ten respiratory isolates of H. influenzae collected during the period 2002–2009 were classified by PCR into gBLNAS (genotype for β-lactamase-negative ampicillin-susceptible), gBLNAR (genotype for β-lactamase-negative ampicillin-resistant) and 3 other genotypes. The associations with host clinical data and antimicrobial suscept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
2
6
1
Order By: Relevance
“…Underlying respiratory diseases did not affect the genotype either in this study. In our previous study on clinical isolates of Haemophilus influenzae from adult patients, we showed that resistance genotype was more likely to be isolated in patients with bronchiectasis and nontuberculous mycobacteriosis among all other respiratory diseases [13]. This finding was not compatible with the present study.…”
Section: Discussioncontrasting
confidence: 96%
See 3 more Smart Citations
“…Underlying respiratory diseases did not affect the genotype either in this study. In our previous study on clinical isolates of Haemophilus influenzae from adult patients, we showed that resistance genotype was more likely to be isolated in patients with bronchiectasis and nontuberculous mycobacteriosis among all other respiratory diseases [13]. This finding was not compatible with the present study.…”
Section: Discussioncontrasting
confidence: 96%
“…Especially, our previous study on H. influenzae where β-lactam antibiotic resistance is also induced by PBP3 mutations focused on drug-resistance genotypes [13] and the results were well in agreement with those of the present study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Isolates with high-level resistance (high-rPBP3) are a major clinical problem in Japan and South Korea [15-17] whereas low-level resistant (low-rPBP3) isolates so far predominate in the rest of the world [4,11,12,14,18-21]. Group II isolates with a characteristic substitution pattern, PBP3 type A (D350N, M377I, A502V, N526K, V547I and N569S) [11], and compatible patterns (identical to PBP3 type A as far as comparison is possible) are particularly common [3,4,9,11,12,16,18,20],[22-25].…”
Section: Introductionmentioning
confidence: 99%